THE EFFECT OF USING ANDROID-BASED LEARNING MEDIA IN INCREASING MOTIVATION AND PHYSICS LEARNING OUTCOMES - Nilsa, Difahar; Sani, Ridwan Abdullah (UNIVERSITAS NEGERI MEDAN, 2022)
The aims of this research study are to analyze change in learning outcomes and student motivation in class X science high school students using android-based learning media and evaluation android-based learning media effect on the physics learning outcomes for class X science high school students. The methods will be using is Quasi-experiment research design with Pretest-Posttest Control Group. The Population and sample of this research is student class X MIA SMA Al-Ulum Terpadu. Questionnaire and intrument test will be used as instrument. The academic performance of the students in this research is limited to increasing motivation and enhancing students learning outcomes in order to assess the product's usefulness. The result of data analysis were the average pretest value for control class was 60.19 and for experimental class was 73.81, after given treatment, the post-test mean value for control class was 88,75 and for experimental class was 90.16. Based on the results, the student's N-Gain, motivation and MANOVA test, the results of the hypothesis obtained are Sig. > 0.05 (0.114, 0.344 > 0.05) which means H0 accepted and H1 is rejected. As a result, utilizing android-based learning media did not have a substantial impact on improving student learning outcomes and motivation.